2017
DOI: 10.1111/mec.14121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of developmental conditions on growth, stress and telomeres in black‐legged kittiwake chicks

Abstract: Early-life conditions can drive ageing patterns and life history strategies throughout the lifespan. Certain social, genetic and nutritional developmental conditions are more likely to produce high-quality offspring: those with good likelihood of recruitment and productivity. Here, we call such conditions "favoured states" and explore their relationship with physiological variables during development in a long-lived seabird, the black-legged kittiwake (Rissa tridactyla). Two favoured states were experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 80 publications
3
51
0
Order By: Relevance
“…For example, younger black‐browed albatrosses produce chicks in poorer condition and with shorter telomeres (Dupont et al, ). Supporting this interpretation, recent studies reported that a larger body size and a better growth rate were associated with longer telomeres in developing birds (Black‐legged kittiwakes Rissa tridactyla : Young et al, ; male Barn swallows Hirundo rustica : Caprioli et al, ; Parolini et al, , but see Common terns Sterna. hirundo , Vedder et al, ) although the relationship between growth and telomere dynamics seems more complex in other study systems (Stier et al, ; Stier, Massemin, Zahn, Tissier, & Criscuolo, , Stier et al, ; reviewed in Vedder et al, ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, younger black‐browed albatrosses produce chicks in poorer condition and with shorter telomeres (Dupont et al, ). Supporting this interpretation, recent studies reported that a larger body size and a better growth rate were associated with longer telomeres in developing birds (Black‐legged kittiwakes Rissa tridactyla : Young et al, ; male Barn swallows Hirundo rustica : Caprioli et al, ; Parolini et al, , but see Common terns Sterna. hirundo , Vedder et al, ) although the relationship between growth and telomere dynamics seems more complex in other study systems (Stier et al, ; Stier, Massemin, Zahn, Tissier, & Criscuolo, , Stier et al, ; reviewed in Vedder et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…In addition to this potential causal link between telomere length and individual quality, telomere length could also be an indirect biomarker of individual quality. Adult telomere length is known to be partly determined by genetic factors (heritability, Asghar Bensch, Tarla, Hansson, & Hasselquist, ; Becker et al, ; Reichert, Rojas et al, ) and developmental conditions (Angelier, Costantini, Blévin, & Chastel, ; Boonekamp, Mulder, Salomons, Dijkstra, & Verhulst, ; Monaghan, ; Nettle et al, ; Young et al, ), which are also known to have long‐term consequences on adult performance (Lindström, ; Metcalfe & Monaghan, ; Monaghan, ). In addition, environmental constraints and life‐history events (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A few past studies report a relationship between accelerated growth, OS and telomere length, in accordance with our results (Bádas et al., ; Geiger et al., ; Stier et al., ). However, others find no relationship between OS and telomere length or attrition (Boonekamp et al., ; Nettle et al., , ; Reichert et al., ; Young et al., ). Boonekamp et al.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies in temperate songbirds during the nestling period have shown that the rearing environment has an influence on telomere attrition rates in early life (e.g., Salmon et al, 2016;Soler et al, 2017). For example, growing up in large broods, high begging effort and low food availability hasten telomere loss in nestlings (Costanzo et al, 2017;Nettle et al, 2017;Young et al, 2017 , 2014;Salmon et al, 2017). The effect of extended parental care in tropical birds on telomere dynamics in fledglings should be further investigated, for example through brood size manipulation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, exposure to poor or stressful environments can lead to accelerated telomere loss in young birds (Costanzo et al, 2017;Haussmann, Longenecker, Marchetto, Juliano, & Bowden, 2012;Herborn et al, 2014;Nettle et al, 2017;Salmon, Nilsson, Nord, Bensch, & Isaksson, 2016;Soler et al, 2017;Young et al, 2017), which can be predictive of decreased survival as nestlings or fledglings (Boonekamp, Mulder, Salomons, Dijkstra, & Verhulst, 2014;Salmon, Nilsson, Watson, Bensch, & Isaksson, 2017;Watson, Bolton, & Monaghan, 2015). For example, exposure to poor or stressful environments can lead to accelerated telomere loss in young birds (Costanzo et al, 2017;Haussmann, Longenecker, Marchetto, Juliano, & Bowden, 2012;Herborn et al, 2014;Nettle et al, 2017;Salmon, Nilsson, Nord, Bensch, & Isaksson, 2016;Soler et al, 2017;Young et al, 2017), which can be predictive of decreased survival as nestlings or fledglings (Boonekamp, Mulder, Salomons, Dijkstra, & Verhulst, 2014;Salmon, Nilsson, Watson, Bensch, & Isaksson, 2017;Watson, Bolton, & Monaghan, 2015).…”
Section: Both Longitudinal and Cross-sectional Studies In Birds Showmentioning
confidence: 99%